ANALYSIS OF IMPLEMENTATION OF COSTS, VOLUMES AND PROFITS AT PT JOBUBU JARUM MINAHASA TBK AND PT KIAN SANTANG MULIATAMA TBK - Mas Ning Zahroh (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to analyze the financial reports of PT Jobubu Jarum Minahasa Tbk and PT Kian Santang Muliatama Tbk for 2021 and 2022. The analysis focuses on contribution margin, break even point, margin of safety, profit planning, operating leverage and shut down point. Data collection methods include library research. The research results show an increase in the profitability of both companies from 2021 to 2022. The analysis provides in-depth insight into the companies' financial and operational performance. It can be concluded that PT Jobubu Jarum Minahasa Tbk has a better contribution margin, break even point and maximum profit than PT Kian Santang Muliatama Tbk. However, PT Kian Santang Muliatama Tbk has more efficient operating leverage. Overall, the analysis shows better financial and operational performance of PT Jobubu Jarum Minahasa Tbk in 2021 and 2022.